Customer satisfaction and perception towards service quality: a case study of Cognis Oleochemicals in Malaysia / Mohd Hashimi Muhamad Hassim - Muhamad Hassim, Mohd Hashimi (Faculty of Business and Management, 2006)
This study is designed to study the customer satisfaction and their perception towards service quality offered by Cognis Oleochemicals in Malaysia. It focused on the level of satisfaction perceived by the customers in terms of product quality, packaging, handling, documents, delivery, and quantity. It is also to determine the customers' perception towards service quality and also the elements of service quality that can influence customer satisfaction. In order to achieve high standard of excellences and also customer satisfaction, it is important for Cognis Malaysia to built long-term relationship with their customer to make them loyal with the company. Cognis also need to create a competitive price for the products that is reliable with the products or service to make the customer accept the price charges and also as one way to compete with other oleochemicals company in Malaysia. The company also must ensure that they can maintain the service quality and trying to improve the services so that the customers make good perception and making them fell that it's easy and fun in doing businesses with Cognis. The finding of this study will hopefully provide further insight in identifying and understand the consumer that are manufacturing companies in Malaysia. Such information will definitely assist Cognis Malaysia in further providing and maintaining service quality as to gives positive perceptions by the customers.